2017
DOI: 10.1016/j.sleep.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Periodic limb movements and restless legs syndrome in children with a history of prematurity

Abstract: Introduction Little is known about which children are at increased risk for restless legs syndrome (RLS) and periodic limb movement disorder (PLMD). Polysomnographic data from the Caffeine for Apnea of Prematurity-Sleep (CAPS) study showed a high prevalence of elevated periodic limb movement index in a cohort of ex-preterm children, but the clinical importance of this finding, such as association with RLS, is unknown. We hypothesized that ex-preterm children would have a high prevalence of RLS and PLMD. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
(38 reference statements)
2
12
0
6
Order By: Relevance
“…En el mismo orden de ideas, Watson et al 45 reportaron que el alcaloide podría estar directamente relacionado con trastornos del sueño, como el insomnio. No obstante, Cielo et al 46 indicaron que la cafeína no eleva la incidencia de otro tipo de trastornos del sueño, particularmente del síndrome de piernas inquietas (SPI).…”
Section: Efectos Físicos De La Cafeínaunclassified
See 1 more Smart Citation
“…En el mismo orden de ideas, Watson et al 45 reportaron que el alcaloide podría estar directamente relacionado con trastornos del sueño, como el insomnio. No obstante, Cielo et al 46 indicaron que la cafeína no eleva la incidencia de otro tipo de trastornos del sueño, particularmente del síndrome de piernas inquietas (SPI).…”
Section: Efectos Físicos De La Cafeínaunclassified
“…De las 20 investigaciones analizadas 16 tuvieron una calificación de calidad fuerte. Las cuatro restantes 45,46,50,53 lograron una calificación moderada. Dos de estos estudios 45,46 corresponden a los efectos fisiológicos, uno 50 versa sobre los efectos cognitivos de la cafeína, y uno más 53 trata sobre los efectos del alcaloide en los trastornos paidopsiquiátricos.…”
Section: Los Instrumentos Que Utilizaron No Fueron Válidos Y/o Confiaunclassified
“…44 Children born preterm also have a higher prevalence of periodic limb movements, which may disrupt their sleep. 47 However, there is no clear understanding of the mechanistic roles of ventilatory-control abnormalities, upper airway muscle hypotonia, palatal deformation (owing to prolonged neonatal endotracheal intubation), adenotonsillar hypertrophy, and obesity in causing sleep-related disturbances. The causes and mechanisms for these conditions during childhood and adolescence remain to be addressed.…”
Section: Sleep Issuesmentioning
confidence: 99%
“…Only half of the studies listed reported a diagnosis of PLMD which was based either on parental report 31 or the current ICSD criteria at publication time. 14,34 Considering these caveats, and using current diagnostic criteria, clinically significant PLMD in children is probably even less common than currently assumed. Periodic limb movement disorder tends to run in families.…”
Section: Epidemiology and Predisposing Factorsmentioning
confidence: 99%